8g+6g-12=-10g+40-2g

Simple and best practice solution for 8g+6g-12=-10g+40-2g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8g+6g-12=-10g+40-2g equation:


Simplifying
8g + 6g + -12 = -10g + 40 + -2g

Reorder the terms:
-12 + 8g + 6g = -10g + 40 + -2g

Combine like terms: 8g + 6g = 14g
-12 + 14g = -10g + 40 + -2g

Reorder the terms:
-12 + 14g = 40 + -10g + -2g

Combine like terms: -10g + -2g = -12g
-12 + 14g = 40 + -12g

Solving
-12 + 14g = 40 + -12g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '12g' to each side of the equation.
-12 + 14g + 12g = 40 + -12g + 12g

Combine like terms: 14g + 12g = 26g
-12 + 26g = 40 + -12g + 12g

Combine like terms: -12g + 12g = 0
-12 + 26g = 40 + 0
-12 + 26g = 40

Add '12' to each side of the equation.
-12 + 12 + 26g = 40 + 12

Combine like terms: -12 + 12 = 0
0 + 26g = 40 + 12
26g = 40 + 12

Combine like terms: 40 + 12 = 52
26g = 52

Divide each side by '26'.
g = 2

Simplifying
g = 2

See similar equations:

| 2x^2+1=2x-x | | 1/2(5-3)=3 | | -2x+4=-8x+1 | | 4*x=453 | | 9+x/8=17 | | 26=30-6a+3a | | 3x=5y-20 | | 1/5x=7 | | 3X^3+4x^2+13x=0 | | 13=b/10 | | 26=30 | | -1/15=x-5/9 | | 1/7+y=-9/14 | | n-m=tw | | 9x+36x-7=9(5x+9) | | 2(r+4/3)=14/3 | | x+17/6=8 | | 8y-7=3(2y+5) | | 50=66-x | | 2x+8=3x-21 | | -6-8(m-7)=20+2m | | x(x-3)=(x+x)+5x+7 | | -2z^2-2z+8=0 | | 4x-7/10-3x=6/10+7/10 | | -4x(x-2)= | | -8(x+6)=6+x | | 6-x=7x+3 | | pr-t=8 | | 3x-9x-7=-6x+6-7 | | -1/2(8x+4)+1/9(54x+45) | | y=(2x^2)/((n^3)+3) | | -6-2n=-(n-2) |

Equations solver categories